THE USE OF DIGITAL TECHNOLOGIES AND INNOVATIVE MARKETING TOOLS TO PROMOTE PROJECTS BASED ON CROWDSOURCING TECHNOLOGIES - D. M. Okhunov (Western European Studies, 2024)
The main goal of crowdsourcing is to reduce costs, but the more important goal is to accelerate innovation. A synergistic effect occurs due to the fact that people are representatives of absolutely different professions involved in the single process of creating a new product. What is crowdsourcing, what is its nature and essence? Why is it gaining popularity all over the world? This article provides answers to these questions
Keywords: digital economy; crowdsourcing; Internet things